Civil-Liability Measures for Transboundary Haze Pollution : A Comparative Study between Thai and Foreign Country Legislation - Boonchaliaw, Worranard (Huachiew Chalermprakiet Law Journal, 2022)
Transboundary haze pollution is a problem that needs to be solved through international cooperation. Transboundary haze pollution in Southeast Asia Wildfires in Indonesia is a major factor. Most of the forest fires are caused by human actions rather than natural actions. The Government of Indonesia could not deal with that problem and Besides When considering International law which can force Indonesia to get liability for creating Transboundary haze pollution it appears that the Paris Agreement and the ASEAN Agreement on Transboundary Haze Pollution which Indonesia is a member of both did not provide any sanctions or stipulations on non-compliance. Singapore considered a country damaged by Transboundary haze pollution from Indonesia has enacted The Transboundary Haze Pollution Act 2014 which is stated to have The civil liability of entity for engaging in conduct (whether in or outside Singapore) which causes or contributes to any haze pollution in Singapore. This article aims to study liability measures for Transboundary haze pollution. Legal measures of Thailand, Singapore and Other interesting countries are analyzed to recommend suitable measures for applying to Thailand.